Neurologic Complications of Fetal Cocaine Exposure - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The effects of prenatal cocaine exposure on intrauterine growth and neurologic function of 253 infants was evaluated prospectively at 1 to 7 days of age at the Division of Pediatric Neurology, College of Physicians and Surgeons, Columbia University, New York.